EVALUATING THE DIAGNOSTIC ACCURACY OF THE NEUTROPHIL-TO-LYMPHOCYTE RATIO IN ACUTE APPENDICITIS: A DISTINCTION BETWEEN COMPLICATED AND UNCOMPLICATED PRESENTATIONS (The Research of Medical Science Review, 2025)
Background: Acute appendicitis is a common surgical emergency with significant diagnostic challenges. The neutrophil-to-lymphocyte ratio (NLR) has been proposed as a potential marker to distinguish between complicated and uncomplicated appendicitis, but its diagnostic accuracy requires further evaluation. Objective: To evaluate the diagnostic accuracy of NLR in acute appendicitis, focusing on its ability to differentiate between complicated and uncomplicated cases. Additionally, the study aims to establish standardized NLR cut-off values and assess its predictive value in combination with clinical parameters. Methods: This retrospective cross-sectional validation study was conducted at the Department of General Surgery, POF Hospital Wah Cantt, from November 2023 to October 2024. A total of 81 patients aged 18–70 years were included using non-probability consecutive sampling. Patients underwent clinical examinations, full blood count (FBC), and histopathological evaluation. Complicated appendicitis was defined based on histopathological findings, with an NLR cut-off of >7 used to indicate complicated cases. Diagnostic accuracy was calculated, including sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). SPSS version 21.0 was used for statistical analysis. Results: Of the 81 participants, 39.5% (n=32) had an NLR >7, associated with complicated appendicitis, while 60.5% (n=49) had an NLR <7. Histopathological examination revealed 71 confirmed appendicitis cases, with a specificity of 100%, sensitivity of 45%, PPV of 100%, and NPV of 20%. NLR >7 was highly predictive of complicated appendicitis but had limited sensitivity. Conclusion: An NLR cutoff of >7 is a highly specific and predictive marker for complicated appendicitis, aligning with previous research. Integrating NLR into clinical practice can improve diagnostic accuracy and optimize patient outcomes, especially in resource-limited settings